2006
DOI: 10.1074/jbc.m508510200
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor Foxo1 Bridges the JNK Pathway and the Transcription Factor PDX-1 through Its Intracellular Translocation

Abstract: It has been shown that oxidative stress and activation of the c-Jun N-terminal kinase (JNK) pathway induce the nucleocytoplasmic translocation of the pancreatic transcription factor PDX-1, which leads to pancreatic ␤-cell dysfunction. In this study, we have shown that the forkhead transcription factor Foxo1/FKHR plays a role as a mediator between the JNK pathway and PDX-1. Under oxidative stress conditions, Foxo1 changed its intracellular localization from the cytoplasm to the nucleus in the pancreatic ␤-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
214
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(222 citation statements)
references
References 62 publications
7
214
1
Order By: Relevance
“…Data are means±SE (n=6). *p<0.05; †p≤0.06; ‡p≤0.07 for difference between genotypes transcription by protecting ROS-induced nuclear localisation of forkhead box O1 (an inhibitor of PDX1 transcription) [46]. The decreased levels of phosphorylated AKT on Thr-308 might attenuate H 2 O 2 -mediated phosphorylation (degradation) of PDX1 [25], but could also inhibit Pdx1 transcription via reduced phosphorylation of forkhead box O1 [9,47].…”
Section: Discussionmentioning
confidence: 99%
“…Data are means±SE (n=6). *p<0.05; †p≤0.06; ‡p≤0.07 for difference between genotypes transcription by protecting ROS-induced nuclear localisation of forkhead box O1 (an inhibitor of PDX1 transcription) [46]. The decreased levels of phosphorylated AKT on Thr-308 might attenuate H 2 O 2 -mediated phosphorylation (degradation) of PDX1 [25], but could also inhibit Pdx1 transcription via reduced phosphorylation of forkhead box O1 [9,47].…”
Section: Discussionmentioning
confidence: 99%
“…Co-localisation of FOXO1 with transcription factors in the developing human fetal pancreas Several studies have demonstrated opposite nuclear vs cytoplasmic localisation of FOXO1 and PDX-1 in murine adult beta cells [7,8]. To better understand the subcellular distribution of FOXO1 and PDX-1 during human fetal pancreatic development, double immunofluorescence and morphometric analyses of FOXO1 in PDX-1 + cells throughout 8-21 weeks of human fetal pancreatic development were performed.…”
Section: Characterisation Of Foxo1 In the Developing Human Fetal Pancmentioning
confidence: 99%
“…Moreover, under oxidative stress conditions, PDX-1 translocates to the cytoplasm of beta cells while FOXO1 moves into the nucleus, resulting in a restriction of beta cell growth and proliferation in order to prevent cellular damage [8]. This differential nuclear vs cytoplasmic localisation of FOXO1 and PDX-1 has been shown in HIT-T15 cells to work through the c-Jun N-terminal kinase pathway [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that FKHR is a negative regulator of insulin synthesis that acts by decreasing PDX1 production [32]. In addition to its important roles in the development and differentiation of pancreatic islets and in beta cell specific gene expression [33], PDX1, an important downstream target of Foxo transcription factors, functions as an essential mediator of the glucose effect on insulin gene expression on differentiated beta cells [14]. In accord, our study demonstrated that PGE 2 could dephosphorylate Foxo transcription factors, prompting them to enter the nucleus and modulate the expression of target genes.…”
Section: Discussionmentioning
confidence: 99%